A privatização dos espaços comuns nas habitações de interesse social: o caso do bairro Granja de Freitas, em Belo Horizonte - Pedro Schultz Fonseca Baptista (2011)
This work aims to investigate the privatizations made in common areas of social housing in the neighborhood Granja de Freitas at the city of Belo Horizonte in the state of Minas Gerais, Brazil. Presents a brief history of housing policy of that city, a pioneer in the country in recognition of slums as part of the city, and its current actions in curative and preventivepolicies. Explains the importance of urban legislation produced in the country, the political scope of popular participation and the nowdays resumption of federal investments in housing and infrastructure. Recalls the concepts explored by John Habraken: housing as a process andnot as a product to request the participation not only in setting policy guidelines, but in the design and management of housing by the user. Identifies the common area, set between the public and private space, an arena for negotiating the residents. Proposes a look that identifiesthe locations in the common area of integration, appropriation and transformation produced by the community. Raises elements of that space through the analysis of different types found in the Granja de Freitas demonstrating its privatization and the conception of democracy and citizenship formed in this space.